Gingival margin alterations and the pre-orthodontic treatment amount of keratinized gingiva - Closs, Luciane Quadrado; Branco, Paula; Rizzatto, Susana Deon; Raveli, Dirceu Barnabé [UNESP]; Rösing, Cassiano Kuchenbecker (FapUNIFESP (SciELO), 2007)
The purpose of this retrospective study was to associate the amount of keratinized gingiva present in adolescents prior to orthodontic treatment to the development of gingival recessions after the end of treatment. The sample consisted of the intra-oral photographs and orthodontic study models from 209 Caucasian patients with a mean age of 11.20 ± 1.83 years on their initial records and 14.7 ± 1.8 years on their final records. Patients were either Angle Class I or II and were submitted to non-extraction orthodontic treatment. Gingival recession was evaluated by visual inspection of the lower incisors and canines as seen in the initial and final study models and intra-oral photographs. The amount of recession was quantified using a digital caliper and the observed post-treatment gingival margin alterations were classified as unaltered, coronal migration of the gingival margin or apical migration of the gingival margin. The width of the keratinized gingiva was measured from the mucogingival line to the gingival margin on the pre-treatment photographs. The teeth that developed gingival recession and those that did not have their gingival margin position changed did not differ in relation to the initial amount of keratinized gingiva (3.00 ± 0.61 and 3.5 ± 0.86 mm, respectively). Paradoxically, teeth that presented a coronal migration of the gingival margin had a smaller initial amount of keratinized gingiva (2.26 ± 0.31 mm). The mean amount of initial keratinized gingiva did not predispose lower incisors and canines to gingival recession.
Keywords: Gingiva; Gingival recession; Orthodontics; keratin; adolescent; analysis of variance; canine tooth; child; classification; dental care; female; gingiva; gingiva disease; histology; human; incisor; male; malocclusion; medical photography; medical record; periodontal disease; retrospective study; Adolescent; Analysis of Variance; Child; Cuspid; Dental Models; Dental Records; Female; Gingival Recession; Humans; Incisor; Keratins; Male; Malocclusion; Photography, Dental; Retrospective Studies; Tooth Movement